عن الفترة (1975 – 2010) ARDL قياس أهم محددات التضخم في الاقتصاد الليبي دراسة قياسية باستخدام منهج - على سعيد عبد الله الشريف (Scientific Journal of University of Benghazi, 2020)
This study aims to determine the factors that affection inflation in Libya in the period (1975- 2010) .The study Used the (ARDL) approach .The results show that there is Negative and significant relationship between inflation and RGDP, and there is positive, and significant relationship between inflation and money supply and oil revenue in the long run.The same results in short run.